Clinical and economic studies of eptifibatide in coronary stenting [Corrigendum] - Pasala T; Sattayaprasert P; Bhat PK; Athappan G; Gandhi S (Dove Medical Press, 2014)
Pasala T, Sattayaprasert P, Bhat PK, Athappan G, Gandhi S. Ther Clin Risk Manag. 2014;10:603–614.The TIMI abbreviation definition of “thrombosis in myocardial infarction” is incorrect for Table 2 on page 606 and Table 3 on page 607. It should read “thrombolysis in myocardial infarction”.Read the original article